Nos caminhos da memória, nas águas do Jaguaribe: memória das enchentes em Jaguaruana-Ce (1960, 1974, 1985) - Silva, Kamillo Karol Ribeiro e (2006)
This work refers the experience of the men and women’s memory residents of the city of Jaguaruana - CE on the inundations happened in the years of 1960, 1974 and 1985. Working with oral source,newspapers and official documents,tries to see her as the full of Rio Jaguaribe they marked the interviewees' memories and the form as these they were counted. Also noticing the material form of the act enunciated the performance, an understanding of the several nuances is looked for and of the several pointed themes for the memoirs. The work is I divide in three chapters. The first chapter back narratives on the moment of the exit and return home during the inundation. In the second chapter, other themes that represented in the interviews as the histories on the work, the diseases and the public politics in times of inundation is discussed. The third chapter is centered in the need of hearing the histories about the construction of the Priest's Villa.